Euconnus Thomson of Japan: redescriptions of species established by Reitter, Sharp and Franz, new synonyms, and summary of current state of knowledge (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2022)
To date, twenty-seven valid species names in the Stenichnini genus Euconnus Thomson have been recognized in the fauna of Japan. The present paper summarizes the current knowledge of Japanese Euconnus, and for the first time properly illustrated redescriptions of E. debilis (Sharp), E. dulcis Sharp, E. fustiger (Sharp), E. impar Sharp, E. japonicus (Sharp), E. oscillans Sharp, and E. raucus Sharp are given, based on type specimens. Lectotypes are designated for Euconnus dulcis Sharp Euconnus lewisii Sharp, Euconnus impar Sharp, Euconnus schoenfeldti Reitter, Scydmaenus japonicus Sharp, and Scydmaenus debilis Sharp. Euconnus schoenfeldti Reitter syn. n. is placed as a junior synonym of E. fustiger (Sharp); E. ohnoensis Hoshina syn. n. is placed as a junior synonym of E. japonicus (Sharp); E. kusunokii Hoshina syn. n. and E. itsuki Hoshina syn. n. are placed as junior synonyms of E. takachihoi Hoshina; and E. hosakae Hoshina, Fukutomi & Watanabe syn. n. is placed as a junior synonym of E. tsugaruensis Hoshina & Arai. Placement of E. lewisii Sharp and E. miyawakianus Franz as junior synonyms of E. fustiger is confirmed. Euconnus iouzensis Hoshina & Nakata, E. kojiroi Hoshina, E. kumejimensis Hoshina, E. miyatai Hoshina, E. sayaka Hoshina, E. sayo Hoshina, E. takachihoi Hoshina, E. touko Hoshina, E. unpini Hoshina, and E. yoshidai Hoshina have been inadequately or inaccurately described and require redescriptions to become identifiable. Status of some of these names (i.e., valid vs. possibly junior synonyms) may be difficult to clarify because the aedeagi of unique holotype males have been improperly prepared and strongly deformed. The current state of knowledge of Japanese Euconnus is discussed and it is concluded that status of many recently described species remains unclear and further work will be difficult because of inadequate descriptions and preparation methods.